ANALISIS PELAPORAN KEUANGAN PENDIDIKAN ANAK USIA DINI (PAUD) KB ASSA’DAH CIKUPA DENGAN PENDEKATAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN - Mishelei Loen, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
Financial reporting is all aspects related to the provision and delivery of financial information. Early Childhood Education (PAUD) is a non-profit organization, in which the source of funds comes from the government and the community. In carrying out activities, Early Childhood Education (PAUD) requires an accounting system to produce financial information as a tool to ensure accountability and transparency in the implementation of educational activities, accounting in education aims for accountability, managerial and supervisory. The purpose of this study was to analyze KB Assa’adah Cikupa's PAUD Financial Reporting with the PSAK 45 approach. In this study the data used was qualitative data, while for data sources using secondary data, the analytical method used was descriptive analysis. Based on the results of the study, concluded that the KB Assa’adah Cikupa PAUD Financial Reporting was not in accordance with the applicable regulations, namely the Statement of Financial Accounting Standards (PSAK) 45